Rape Victim Advocates Experiences With Law Enforcement in the Emergency Room. (December 2018) - Long, LaDonna M.
One of the first people a sexual assault survivor will encounter in the emergency room is a specially trained rape victim advocate. Along with rape victim advocates, many survivors will come across law enforcement in the emergency room. This study explores rape victim advocates perception of how survivors are treated in the emergency room by law enforcement. Data from interviews with 23 female advocates indicate a complex relationship that includes positive interactions with police as well as victim blaming and a lack of knowledge about how sexual assault affects survivors. Suggestions for future research are provided.